2017
DOI: 10.1371/journal.pone.0185067
|View full text |Cite
|
Sign up to set email alerts
|

Excitability is increased in hippocampal CA1 pyramidal cells of Fmr1 knockout mice

Abstract: Fragile X syndrome (FXS) is caused by a failure of neuronal cells to express the gene encoding the fragile mental retardation protein (FMRP). Clinical features of the syndrome include intellectual disability, learning impairment, hyperactivity, seizures and anxiety. Fmr1 knockout (KO) mice do not express FMRP and, as a result, reproduce some FXS behavioral abnormalities. While intrinsic and synaptic properties of excitatory cells in various part of the brain have been studied in Fmr1 KO mice, a thorough analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
(87 reference statements)
2
14
0
Order By: Relevance
“…Spontaneous network properties are influenced by active and passive membrane properties, and indeed, many studies have reported that in rodent models the loss of expression of FMRP leads to cortical hyperexcitability [9,[12][13][14]36]. It is becoming increasingly clear that FXS pathophysiology as assessed in rodent models shows complex diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous network properties are influenced by active and passive membrane properties, and indeed, many studies have reported that in rodent models the loss of expression of FMRP leads to cortical hyperexcitability [9,[12][13][14]36]. It is becoming increasingly clear that FXS pathophysiology as assessed in rodent models shows complex diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Given the distinct patterns of spontaneous burst firing in neurons lacking FMRP compared to control neurons, we sought to determine whether this was due to differences in either intrinsic or synaptic properties between cell lines. Indeed, rodent models of FXS have reported that some classes of principal neurons lacking FMRP display altered intrinsic excitability [9,[12][13][14]36] although others have not observed difference in these parameters [15,37] most likely reflecting the fact that where differences do occur these are cell-type specific, rather than a generalized alteration in intrinsic excitability due to the loss of expression of FMRP. However, human neurons lacking FMRP have been reported to exhibit a considerably compromised ability to generate trains of action potential firing in response to depolarizing current injections [21].…”
Section: Despite Different Spontaneous Action Potential Firing Pattermentioning
confidence: 99%
“…For instance, while dendrites of hippocampal neurons from Fmr1 −/y mice display increased HCN1-channel 24 expression and reduced input resistance (Brager et al, 2012 ), dendrites of cortical layer 5 neurons show the opposite (Zhang Y. et al, 2014 ). The intrinsic membrane excitability of cortical layer 4 excitatory neurons is exaggerated (Gibson et al, 2008 ), while that of excitatory hippocampal neurons is normal (Deng et al, 2013 ; Luque et al, 2017 ). Hippocampal neurons demonstrate significantly longer action potential durations and higher firing frequencies in the absence of FMRP than under normal conditions (Luque et al, 2017 ), whereas layer 2/3 neurons in the prefontral cortex present significantly narrower and taller action potentials in Fmr1 −/y mice than in their wildtype litter mates (Routh et al, 2017 ).…”
Section: The Fragile X Syndrome — Of Micementioning
confidence: 99%
“…The intrinsic membrane excitability of cortical layer 4 excitatory neurons is exaggerated (Gibson et al, 2008 ), while that of excitatory hippocampal neurons is normal (Deng et al, 2013 ; Luque et al, 2017 ). Hippocampal neurons demonstrate significantly longer action potential durations and higher firing frequencies in the absence of FMRP than under normal conditions (Luque et al, 2017 ), whereas layer 2/3 neurons in the prefontral cortex present significantly narrower and taller action potentials in Fmr1 −/y mice than in their wildtype litter mates (Routh et al, 2017 ). Although both alterations indicate enhanced excitability, the sharpened action potentials observed the cortex of Fmr1 −/y mice are in contrast with the broadened action potentials seen in the hippocampus.…”
Section: The Fragile X Syndrome — Of Micementioning
confidence: 99%
“…Multiple previous studies have found hyper excitability in hippocampus in FXS model mice (Deng and Klyachko, 2016;Luque et al, 2017). However, (Brager et al, 2012) found a lowering of Input Resistance for KO CA1 cells indicative of reduced excitability.…”
Section: Comparison With Previously Published Studiesmentioning
confidence: 83%